Analisis Pengelolaan Dana Desa di Decamatan Sungai Raya Kabupaten Kubu Raya (Studi Kasus Pada Desa Sungai Raya Dalam dan Desa Sungai Ambangah) - B2052162011, Sri Mulyanti (Jurnal Ekonomi Daerah (JEDA), 2019)
This research was conducted to find out and analyze how the use and management of village funds in the developed and backward villages in Kuburaya District, then to analyze whether the management of the village fund has a difference. Since the government has arranged the management and use of the village funds in accordance with the typology type) village. This research was conducted with the sample of the advanced village is Sungai Raya Dalam Village and the sample of the remaining village is Sungai Ambangah Village for the use of village fund in 2017.The results show that in the management of village funds in the developed villages (Sungai Raya Dalam) and underdeveloped villages (Ambangah River) in planning, implementation, administration, reporting and accountability have involved the community, but in reporting responsibility beyond the specified time limit. For the use of village funds, the underdeveloped village (Ambangah River) has used village funding as priority as the underdeveloped village that is for the construction of basic facilities, while the use of village funds in Sungai Raya Dalam village is not appropriate, because the utilization of village funds has not supported the creation of wairausahawan and energy professionals and the expansion / expansion of village economic enterprises, as most of the village funds for the construction of basic facilities such as villages are left behind. Meanwhile, based on the results of different test of village fund management, it is concluded that statistically there is difference of village fund management in developed village (Sungai Raya Dalam) and left behind village (Ambangah River) t count equal to 3,282 and significant at alpha 0,002 (0,2%).Keywords: Planning, Implementation, Management, Reporting and Accountability